Association Between Platelet Reactivity and Long-Term Bleeding Complications After Percutaneous Coronary Intervention According to Diabetes Status - Cavallari, Ilaria; Patti, Giuseppe; Maddaloni, Ernesto; Veneziano, Francesco; Mangiacapra, Fabio; Ricottini, Elisabetta; Buzzetti, Raffaella; Ussia, Gian Paolo; Grigioni, Francesco (The American journal of cardiology, 2022)
The relation between diabetes mellitus (DM) and bleeding complications after percutaneous coronary intervention (PCI) is controversial. This study investigates the role of low platelet reactivity (LPR) in the bleeding risk stratification of patients who underwent PCI according to DM status. A total of 472 patients who underwent PCI on aspirin and clopidogrel were included retrospectively. Platelet reactivity was assessed using the VerifyNow P2Y(12) assay. LPR was defined as platelet reactivity unit ≤178. The primary end point was the occurrence of any bleeding at 5 years stratified by DM status and LPR. DM was present in 30.5% of patients. LPR was less frequent in patients with DM (p = 0.077). Overall, 11.9% of patients experienced a bleeding complication at 5 years. The incidence of bleeding did not differ in subjects with and without DM (p = 0.24). LPR had a similar value for stratifying the increased bleeding risk in patients with and without DM (interaction p between DM and LPR 0.69). A stepwise increase in the crude rates of bleeding complications was observed across patients with and without LPR and DM (log-rank p = 0.004), with those affected by both conditions having the highest crude incidence rate. In conclusion, on top of aspirin, approximately 1/3 of patients who underwent PCI on clopidogrel have LPR. Assessment of LPR provides a significant incremental value for predicting bleeding irrespective of DM status. Although the presence of DM per se does not increase the incidence of hemorrhagic complications, the coexistence of DM and LPR identifies the subgroup with the highest bleeding risk.